ZIS Institutions and Inclusive Asset-building Policy Agenda - Davy Hendri (Institute for Research and Community Empowerment (LPPM TAZKIA), 2012)
Objective – This study will try to describe inclusive asset building (further abbreviated as IAB ) concept which proposed by Michael Sherreden and it’s implementation as the main agenda of ZIS institutions activities. Anti-poverty proposals from various parties include government agencies, private and public, generally focusing on income subsidy policy to encourage public demand over the minimum edge (borderline poverty) of live well.Method - Library research is applied since this paper relies on secondary data by thoroughly reviewing the most relevant literature. This will be elaborated starting from the introduction of mechanisms and IAB programs in the main activities of ZIS institutions. In addition, several prerequisites adjustments and strengthening either in terms of institutional, organizational capacity and management needs to be conducted by the ZIS institutions so that this study will achieve as expected.Results -.Combination of income support with the asset accumulation such as subsidise saving for the poor will be more long-term. Which is expected to help out the poor from socio-economic alienation. Through the implementation of this concept, ZIS institutions have a chance to heighten the leverage of their role in poverty alleviation.Conclution – All resources, either internal and external that have been built by LAZ during these days, is a valuable capital to initiate the paradigm shift. Also, the benefits of institutional characteristics and closely relationship with the clients (mustahik) could be additional notes.Keywords: Poverty, Income Subsidy, Inclusive Asset